Hepato-renal syndrome - K. U. Mugiyo (Indonesian Pediatric Society, 1981)
Herein we report a case of hepato-renal syndrome, the diagnosis established was based all chronic hepatic disease accompanied by impairment of renal function and histopathologic changes. Clinical pictures and histologic examination of the liver showed that the hepatic disease was an obstructive jaundice due to congenital malformation. On the other hand, clinical pictures, laboratory examination, renogram, light microscopy of the kidney showed that there were severe impairment of renal function and tubular changes together with focal interstitial fibrosis.